On the Boundedness and the Stability of Solution to Third Order Non-Linear Differential Equations - Ogundare, B. S.; Okecha, G. E. (2014)
In this paper we investigate the global asymptotic stability, boundedness as well as the ultimate boundedness of solutions to a general third order nonlinear differential equation, using complete Lyapunov function.